A Brillouin scattering-based fast temperature measurement method for ADSS of distribution IoT in electricity. Issue 1 (1st April 2022) - Yang, Qingsheng; Chen, Zhiming
Abstract: In order to decrease time of temperature measurement for optical fiber in ADSS (all-dielectric self-supporting cable) of distribution IoT (Internet of Things) in electricity, the slope-assisted method is applied to its temperature demodulation. According to the introduction of the Brillouin scattering-based optical fiber temperature measurement method, the basic principle of Brillouin frequency shift measurement method based on the spectra fitting algorithm and the slope-assisted method is analyzed. Based on simulated Brillouin spectra with different signal-to-noise ratios (SNRs), the measurement time and accuracy of the spectra fitting algorithm and the slope-assisted method are compared. The results indicate that when if the SNR of Brillouin spectra is not less than 35 dB, the mean error of temperature measurement by the slope-assisted method is less than 0.5°C, which is slightly larger than the error of the spectra fitting algorithm, but the spectra measurement time is only 1/17 of that of the latter.